2014
DOI: 10.3389/fenvs.2014.00028
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of hair dye by lignocellulosic waste materials from contaminated waters

Abstract: Basic yellow 57 (BY57) was chosen as a model hair dye due to its prevalence in cosmetics wastewaters. This study proposes the use of lignocellulosic materials like spent tea leaves of peppermint (PM), chai tea (CT), and chamomile (CM) as raw adsorbents for the removal of BY57 from contaminated solutions. Batch adsorption experiments were carried out at room temperature to achieve the maximum adsorption capacity. Results indicate that the highest removal is achieved at pH 6-8, with a minimum adsorbent mass of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
1
8
1
2
Order By: Relevance
“…This could be explained by the +2 charge of calcium ions, which may interrupt the caffeine/adsorbent interactions. This behavior has been also observed with other pollutants like drugs, dyes and heavy metals [12,17,18].…”
Section: Role Of Salts On the Removal Efficiency Of Caffeinementioning
confidence: 56%
See 2 more Smart Citations
“…This could be explained by the +2 charge of calcium ions, which may interrupt the caffeine/adsorbent interactions. This behavior has been also observed with other pollutants like drugs, dyes and heavy metals [12,17,18].…”
Section: Role Of Salts On the Removal Efficiency Of Caffeinementioning
confidence: 56%
“…Previous work indicates that marine algae can be potentially used for the removal of copper (II) ions [11], sulfa drugs [12] and other heavy metals [13] from aqueous solutions. A more sustainable research has also demonstrated that spent chai tea leaves are good candidates for the removal of heavy metals from contaminates solutions [14] and artificial dyes [15][16][17]. More recent work has encapsulated spent tea leaves into chitosan hydrogel beads for the removal of cupric ions from solutions [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This CO 2 has an effect on the greenhouse effect in the long-term range [6]. Recent efforts have been invested in the use of naturally-occurring materials, such as marine algae, products from seashells, and lignocellulosic materials in their raw state as potential adsorbents of water pollutants [7][8][9][10]. For example, hydrogel beads of chitosan and alginate have been used in the removal of caffeine [11], even in the presence of salts and other interfering substances.…”
Section: Introductionmentioning
confidence: 99%
“…These models are based either on solution concentration, e.g., first-order, second-order reversible or irreversible and pseudo-first, pseudo-second order or on adsorption efficiency, e.g., Lagergren's first-order equation, Zeldowitsch's model and Elovich's equation (Ho and McKay, 1999;Ho, 2006a,b;Dari et al, 2015;Zahir et al, 2015).…”
Section: Introductionmentioning
confidence: 99%